Effect of High-Dose Continuous Albuterol Nebulization on Clinical Variables in Children With Status Asthmaticus*. Issue 2 (February 2015) - Phumeetham, Suwannee; Bahk, Thomas J.; Abd-Allah, Shamel; Mathur, Mudit
Abstract : Objectives: Continuous albuterol nebulization is generally administered at 2.5–20 mg/hr at most centers. We examined the effect of high-dose (75 or 150 mg/hr) albuterol on clinical variables in children with status asthmaticus. Design: Retrospective analysis of inpatient medical records and prospectively collected computerized PICU respiratory therapy database. Setting: Twenty-five-bed multidisciplinary PICU in a tertiary care children's hospital. Patients: Children admitted to the PICU between January 2006 and December 2007 with status asthmaticus receiving high-dose continuous albuterol nebulization. (Those with cerebral palsy, cardiac pathology, and ventilator dependence were excluded.) Interventions: Chart review for PICU length of stay, albuterol dose, duration of nebulization, occurrence of chest pain, vomiting, tremors, hypokalemia (serum potassium < 3.0 mEq/L), and cardiac arrhythmia. Maximal heart rate, lowest diastolic blood pressure, and mean arterial pressure were compared to the variables at initiation of therapy and at hospital discharge. Measurements and Main Results: Forty-two patients (22 boys and 20 girls) received high-dose continuous albuterol nebulization. Twenty-three received 75 mg/hr and 19 received 150 mg/hr (3.7 mg/kg/hr [interquartile range, 2.4–5.8 mg/kg/hr]) for a duration of 22.3 hours (interquartile range, 6.6–31.7 hr). Heart rate increased and diastolic blood pressure and mean arterial pressure were significantly lower during nebulization compared to initiation of therapy or at hospital discharge ( p < 0.05). No patient required fluid resuscitation or inotropic support, and one had self-limited premature ventricular contractions. Hypokalemia occurred in five of 33 patients who had serum electrolytes measured but did not require supplementation. One patient required endotracheal intubation after initiation of nebulization, and seven patients (16.7%) received noninvasive ventilation. PICU length of stay was 2.3 ± 1.7 days; there were no deaths. Conclusions: High-dose continuous albuterol nebulization is associated with a low rate of subsequent mechanical ventilation and fairly short PICU length of stay without significant toxicity. Prospective studies comparing conventional and high-dose albuterol nebulization are needed to determine the optimum dose providing maximum efficacy with the least adverse effects.